2023
DOI: 10.3390/ijms24065348
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antimicrobial Protein S100A15 Expression by Oral Microbial Pathogens Is Toll-like Receptors-Dependent Activation of c-Jun-N-Terminal Kinase (JNK), p38, and NF-κB Pathways

Abstract: The antimicrobial protein S100A15 belongs to the S100 family, which is differentially expressed in a variety of normal and pathological tissues. Although the function of S100A15 protein has been discussed in several studies, its induction and regulation in oral mucosa, so far, are largely unknown. In this study, we demonstrate that S100A15 is induced by the stimulation of oral mucosa with gram− or gram+ bacterial pathogens, as well as with the purified membrane components, namely lipopolysaccharides (LPS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…ASK1, an apoptotic signal-regulating kinase, can be activated by stress-related stimuli to activate MEKK4 and MEKK3, leading to p38 activation and the induction of apoptosis through signals associated with the mitochondrial cell death pathway. 24 , 25 , 27 We observed elevated levels of ASK1 and MEKK3 in the SNP group; however, treatment with curcumin attenuated their expression ( Figure 5D–F ). Other studies have demonstrated that the inhibition of pkcδ expression and phosphorylation can effectively suppress the activation of the p38/MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…ASK1, an apoptotic signal-regulating kinase, can be activated by stress-related stimuli to activate MEKK4 and MEKK3, leading to p38 activation and the induction of apoptosis through signals associated with the mitochondrial cell death pathway. 24 , 25 , 27 We observed elevated levels of ASK1 and MEKK3 in the SNP group; however, treatment with curcumin attenuated their expression ( Figure 5D–F ). Other studies have demonstrated that the inhibition of pkcδ expression and phosphorylation can effectively suppress the activation of the p38/MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 88%
“…On the basis of the enrichment results and previous studies, we speculated that oxidative stress, apoptosis, and the p38 mitogen-activated protein kinase (p38/MAPK) signaling pathway play important roles in the progression of OA. 24 , 25 According to the aforementioned data, the core targets were separately imported into the AutoDock Vina 1.1.2 software and docked with curcumin ( Figure 1E ). Hydrogen bonds formed between the molecules are represented by yellow dotted lines in Figure 1E , and the relevant binding energies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%